'Event, memory, metaphor': The 1984 anti-Sikh pogroms in India. (2nd October 2022) - Ray, Reeju
ABSTRACT: In this essay, Jaspreet Singh's novel Helium is read as a historical text alongside government reports of the pogroms, media reports of the event, and oral ethnographies of survivors of 1984. Helium offers an understanding of how the memory archive challenges continued impunity of perpetrators of state violence. Impunity is embedded in the state's judicial processes, in a lack of public accountability, in forgetting, and in repetition. The survivors present a profound challenge to impunity by their refusal to accept the logic of badla or revenge.